Child abuse in sport : critical perspectives - Hartill, Mike; Rulofs, Bettina (Research in the sociology of sport ;, 2025)
International attention on the abuse and exploitation of children and athletes in sport and its prevention has never been higher, as more cases of child abuse in sport have emerged across the globe in recent years. While there have been many developments in research, policy, and practice in this area, we are not yet close to putting an end to endemic child abuse within some sport environments. Against this dynamic landscape, this edited collection is a timely critical reflection on this field, its trajectory, and contemporary developments within it. The chapters are theoretically informed, sociological analyses of abuse, violence, and exploitation of children in sport that critically interrogate the social and cultural terrain in which these interpersonal violations occur. Elucidating deeper understanding of the problem of child abuse in sport and the various responses to it, both academic and policy-based, the collection uses a critical sociological lens and various distinct theoretical lenses to provide the conceptual tools to problematise the practice and administration of youth sport. Engaging critically with the topic, the authors identify weaknesses, limitations, and omissions within current scholarship, thereby individually and collectively providing an agenda for future research in this field. Child Abuse in Sport serves as an essential resource for sociology of sport students and researchers in this field, providing a state-of-the-art review of an urgent and rapidly growing area of sport scholarship and governance.